Bridging novelty and familiarity-based recognition memory: A matter of timing. Issue 9 (26th November 2017) - Delhaye, Emma; Bastin, Christine; Moulin, Christopher J.A.; Besson, Gabriel; Barbeau, Emmanuel J.
ABSTRACT: Novelty detection is essential to adapt to changes. However, the relationship between novelty detection and visual recognition memory remains unclear. To characterize the temporal dynamics of novelty and its connection to familiarity, we probed early behavioural performance of novelty and familiarity in 31 participants using a speeded go/no-go recognition task with a 600-ms response deadline. Responses to familiarity and novelty produced symmetrical biases and correlated accuracies and biases, but novelty decisions were less accurate and had slower minimal reaction times (410 ms). These processes thus appear to be independent, as suggested by a more efficient system in the case of familiarity, but with common factors bringing overlapping contributions to both processes. This may possibly be explained by the more fluent processing of repeated stimuli, but with familiarity and novelty potentially relying on one decision criterion, as suggested by the correlated and remarkably symmetrical biases. This study supports models that conceptualize novelty and familiarity decisions as two partly overlapping processes.